Borate single crystals for polyfunctional applications: production and properties - Grinyov, B.V.; Dubovik, M.F.; Tolmachev, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Literature data and results of authors' studies are rewieved concerning structure, growing conditions, non-linear optical, piezoelectric and spectral characteristics of borate single crystals Li₂B₄O₇, LiB₃O₅, b-BaB₂O₄, LaB₃O₆, Li₆Gd(BO₃)₃. A high scintillation efficiency of LaB₃O₆ and Li₆Gd(BO₃)₃:Ce single crystals as well as the high thermostimulated luminescence yield of Li₂B₄O₇: (Ce, Eu, Tm) ones have been demonstrated.